¿Es representada apropiadamente la conservación de la biodiversidad en los estudios de valoración económica? - Dávila, José (2022)
In the last two decades, stated preference methods have been used to estimate the willingness to pay for biodiversity conservation. However, the results of these methods can present phenomena that contradict economic theory, such as utility and welfare theory. Based on a systematic review, the characteristics of the Contingent Valuation and Choice Experiment applications were identified for the case of biodiversity, whose conservation is a public good. It was identified that the conservation of biodiversity was studied mainly from representations of species (flora and fauna) and habitats. The studies that include the representation of functionality contribute to the non-appearance of scope insensitivity, which would support the use of their results in environmental public policies.